2014
DOI: 10.1002/ece3.1128
|View full text |Cite
|
Sign up to set email alerts
|

Timing matters: species‐specific interactions between spawning time, substrate quality, and recruitment success in three salmonid species

Abstract: Substratum quality and oxygen supply to the interstitial zone are crucial for the reproductive success of salmonid fishes. At present, degradation of spawning grounds due to fine sediment deposition and colmation are recognized as main factors for reproductive failure. In addition, changes in water temperatures due to climate change, damming, and cooling water inlets are predicted to reduce hatching success. We tested the hypothesis that the biological effects of habitat degradation depend strongly on the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 66 publications
0
29
1
Order By: Relevance
“…Our results confirm that higher rates of fine sediment accumulation also had a negative effect on hatching rates of the nase as a cyprinid species, both in the incubation systems and the reference incubation boxes on site, even though the incubation period for nase eggs is substantially shorter compared to salmonids. This might also be of evolutionary relevance, as found for the Danube salmon (Hucho hucho L.) and the brown trout (Salmo trutta L.) (Sternecker, Denic, & Geist, 2014;Sternecker & Geist, 2010). Threshold effects observed in other studies for salmonids revealed that survival rates dropped rapidly when the percentage of the most influential fine sediment class (<0.85 mm) was greater than 10% (Jensen, Steel, Fullerton, & Pess, 2009), resulting in oxygen deficits within the interstitial zone that can also impair nase development (Keckeis et al, 1996).…”
Section: Factors Determining the Hatching Success Of Nase Eggsmentioning
confidence: 81%
See 1 more Smart Citation
“…Our results confirm that higher rates of fine sediment accumulation also had a negative effect on hatching rates of the nase as a cyprinid species, both in the incubation systems and the reference incubation boxes on site, even though the incubation period for nase eggs is substantially shorter compared to salmonids. This might also be of evolutionary relevance, as found for the Danube salmon (Hucho hucho L.) and the brown trout (Salmo trutta L.) (Sternecker, Denic, & Geist, 2014;Sternecker & Geist, 2010). Threshold effects observed in other studies for salmonids revealed that survival rates dropped rapidly when the percentage of the most influential fine sediment class (<0.85 mm) was greater than 10% (Jensen, Steel, Fullerton, & Pess, 2009), resulting in oxygen deficits within the interstitial zone that can also impair nase development (Keckeis et al, 1996).…”
Section: Factors Determining the Hatching Success Of Nase Eggsmentioning
confidence: 81%
“…To date, research on the effects of fine sediments on fish has been concentrated on species of relatively few families, notably salmonids (Kemp, Sear, Collins, Naden, & Jones, 2011;Sternecker et al, 2013). This might also be of evolutionary relevance, as found for the Danube salmon (Hucho hucho L.) and the brown trout (Salmo trutta L.) (Sternecker, Denic, & Geist, 2014;Sternecker & Geist, 2010). This might also be of evolutionary relevance, as found for the Danube salmon (Hucho hucho L.) and the brown trout (Salmo trutta L.) (Sternecker, Denic, & Geist, 2014;Sternecker & Geist, 2010).…”
Section: Factors Determining the Hatching Success Of Nase Eggsmentioning
confidence: 99%
“…It is thus not surprising that several publications reported on low or degrading biological functionality of this river (e.g. Sternecker et al ., ; Pulg et al ., ; Sternecker et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…(), olfactory cues may contribute to mate choice, shoaling behaviour, and kinship. Examples of segregated spawning contributing to genetic divergence have been observed in several other fishes – salmonids (Vähä et al ., ; Sternecker, Denic & Geist, ), whitefish (Bernatchez et al ., ), smallmouth bass (Stepien, Murphy & Strange, ), and herring (McPherson, Stephenson & Taggart, ) – and thus is worthy of further investigation in perch and roach.…”
Section: Discussionmentioning
confidence: 99%